The dynamics of newspaper operations in Iloilo City the covering of human rights violation reports of selected local newspaper during the Gloria Arroyo administration 2001-2010. - Garcia, Aika Fore M.
This study sought to describe and analyze the human rights violations coverage of local newspapers in Iloilo City focusing on the case of the Daily Guardian and Panay News during the Gloria Arroyo Administration (2001-2010). The objectives of this study are: to describe and analyze the human rights coverage of local newspapers, to identify the challenges and restraints experienced by the journalists and editors of the local newspapers; and lastly, to identify the feedback and reactions of the readers on the human rights violation reports of the local newspapers. This study was conducted in Iloilo where the main offices of the selected local newspapers are located. Six journalists, and editor and a staff participated in the study. The researcher used interview questionnaire, newspaper analysis and secondary data in order to give an in-depth understanding and analysis of the study. The data gathered were collected, summarized and analyzed. Results of the study showed that the local newspapers are faced with number of issues that affects their human rights violation coverage. Despite these issues, local newspapers still gives ample attention to human rights violation reports since this issue also affects their very existence. The participants in this study have condemned the human rights violation during the Gloria Arroyo administration. They have witnessed, if not personally experienced, the threats and harassment of media practitioners. Some of the participants are victims of the abuses of government officials or those who have close ties with people in power. The public is most of the time impassive to human rights violation reports. Those usually react to the human rights violation reports of the local newspapers are human rights advocates and media organizations.